Determinants of Local Investment: Case Study in Provinces in Indonesia - Jamzani Sodik; Didi Nuryadin (Universitas Islam Indonesia, 2008)
The main purpose of this research is to test the determinants of local investment in 26 provinces in Indonesia since 1993-2003 using dynamic panel method. Factors affecting local investment in Indonesia are market size indicator which is growth rate PDRB (X1), infrastructure indicator i.e. number of electricity capacity (X2), indicator spatial which is deensity (X3), indicator manpower that is labour force (X4) and wages/UMP (X5), and last of economic indicators that is export/ level of chartered investment counsel openness (X6). The result concludes that all variables applied in stationary research has at data level (I0), equally all variables have owned degree of the same integration. Result of panel test cointegration using parametric approach indicates that Group rho-Statistic coefficient is 8432 while Group PP-Statistic coefficient co integration is 9193. The coefficient co integration by using Group ADF-Statistic is 2540. Probability of each testing method indicates that variable applied by cointegrating at level of significance at 5%. From total 7 testing panel, got result that all research variable of co integrating or on a long term research variable has direction of the same movementKeywords: investments, panel dynamic, unit root panel, and cointegration panel